Design and Performance of Swirl Flow Microbubble Generator - Syaeful Alam, Hilman; Gita Redhyka, Grace; ., Bahrudin; Tri Sugiarto, Anto; Ibnu Salim, Taufik; Robbihi Mardhiya, Inda; ., . (International Journal of Engineering and Technology, 2018)
The design of a microbubble generator that has high efficiency and good performance is still a challenge today, especially for a large scale application. In this study, CFD simulation based on the transient operation was used to predict the characteristics of a fluid flow as a reference in the design process. To analyze the performance of the swirl flow microbubble generator, particle image velocimetry (PIV) was used to characterize the dimension and distribution of microbubbles. Based on the simulation results, CFD was able to visualize the mixing process and the fluid characteristics of the gas-liquid flow in a swirl flow microbubble generator. Air self-suction mechanism in a microbubble generator nozzle was successfully formed by a negative pressure in the central axis area of the nozzle due to a swirl flow of water. It shows that a swirl flow microbubble generator can work efficiently and doesn’t need any other devices to deliver air into the system. Based on the PIV measurement, the microbubbles were successfully formed with the radius averaged of 25 µm for both air mass flow rate of 0.25 l/min and 1 l/min. However, the smaller the mass flow rate of air, the more the number of microbubbles generated.
Keywords: CFD; microbubble; unsteady; swirl flow; particle image velocimetry.